A summary of recent Kansas State University research on the metabolism of supplemental niacin in the rumen of cattle - Bartley, E.E.; Riddell, D.O.; Arambel, M.A.; Dennis, S.M. (Kansas State University. Agricultural Experiment Station, 2010)
Benefits have been shown under certain conditions when niacin is added to the diets of beef cattle, dairy cattle or sheep. We attempted to find out what effects added niacin has on the rumen fermentation, and conversely, how the rumen metabolizes niacin.
Keywords: Beef; Niacin; Fermentation; Rumen